The virtues of collective gatherings: A study on the positive effects of a major scouting event. Issue 3 (26th December 2019) - Bouchat, Pierre; Rimé, Bernard; Van Eycken, Roxanne; Nils, Frédéric
Abstract: The present study addresses, in a highly ecological setting, the short‐ and long‐term psychosocial consequences of participation in a major scouting event. Using a quasi‐longitudinal design comprising three measures taken over two‐and‐a‐half months (i.e., baseline level; within the 24 hr following the event; 10 weeks after the gathering), we show that participation in this collective gathering was followed by a series of positive effects at the psychosocial level. More precisely, we noticed an increase in the scout's levels of social integration, and individual and social well‐being after their participation in the gathering. Further, in line with a central tenet of the neo‐Durkheimian model of collective processes, the results stress the key role of perceived emotional synchrony in the prediction of the outcomes. Higher perceived emotional synchrony during the gathering was associated with stronger in‐group identification, identity fusion, pride, openness to experience, self‐esteem, positive affects, and adhesion to specific scouting values. Finally, we found that the effects of participation lasted more than a few days and were predicted by the level of perceived emotional synchrony. These findings are the first to show that positive effects of participation in a collective event last for at least ten weeks.